A case of autumn mating in the Apennine Brown Bear (Ursus arctos marsicanus) - TOSONI, Elisabetta; BOITANI, Luigi; CIUCCI, Paolo; Paolozzi, Germano; Trella, Ezechia (ASSOC TERIOLOGICA ITAL, 2011)
Although the breeding season of brown bears generally occurs during early spring or summer, a few incidents of autumn mating have been recently documented in British Columbia and Japan. Considering the rarity, yet the relevance, of these events, we report a case of autumn courtship and mating in the Apennine brown hear observed as late as 3 November 2010 in the Abruzzo Lazio and Molise National Park, central Italy. Mating was preceded and followed by muzzle sniffing and play lighting, and involved an adult female associated with a cub. During the 20-min observation, the female did not display cub defence behaviour, nor the adult male acted aggressively toward the cub. We briefly discuss this observation on theoretical grounds, including the potential meaning of late breeding for this small bear population.